Community perception and assessment of public toilets in Kuala Lumpur among users of KTM commuter public toilet - Mohamad Isham, Nurul Huda; Abdul Rahman, Haliza; Mohamed Zain, Izzah Nadhirah (Universiti Putra Malaysia Press, 2022)
Introduction: Some public toilets in Malaysia are still far from the clean category, with an unpleasant smell, faulty and insufficient basic amenities. Poor sanitation continues to be a global issue, contributing to the spread of life-threatening illnesses and pollution of land and water. One of the United Nations Sustainable Development Goals (SDGs), Goal 6, Clean Water and Sanitation, plays a role in addressing this issue. Therefore, this study aims to determine the perception and assessment of the public toilets in Kuala Lumpur. Methods: A cross-sectional study design was used among the public toilet user of Keretapi Tanah Melayu (KTM) Commuter. Respondents (n=112) were obtained through convenience sampling among the commuter KTM public toilet users in Kuala Lumpur. Descriptive statistics were used to analyze the sociodemographic information, general questions, perception, and assessment of public toilets. Pearson correlation test was used to determine the association between perception and assessment of public toilets. Results: The results showed that most of the elements of public toilet facilities such as door, floor, and walls were rated neutral except for the toilet seat that was rated dirty (40.2%). The majority of respondents had a moderate perception of public toilets (73.2%). The findings also showed no association between perception and assessment of public toilets (p=0.139, r=0.141). Conclusion: In conclusion, Keretapi Tanah Melayu (KTM) Commuter public toilet users in Kuala Lumpur have a moderate perception, and they mostly suggested that public toilet user is the most responsible for the cleanliness of the public toilet.